Financial toxicity in patients with advanced solid malignancies participating in early-phase clinical trials. Issue 28 (1st October 2022) - Blanter, Julia; Werner, Michael; Kier, Melanie Wain; Hapanowicz, Olivia; Itani, Muhieddine; Ahmad, Maham; DeMerchant, Mandy; Eder, Joseph Paul; Galsky, Matt D.; Hammad, Ashley; King, Paula; Lachowicz, Michael; et al.
Abstract : 267 Background: Financial toxicity (FT) adversely influences patient quality of life and is a barrier to clinical trial enrollment. Early phase clinical trials (EPTs) primarily recruit patients with advanced malignancies who have received all standard therapy regimens and may thus have high levels of FT. We sought to assess baseline FT and its association with clinicodemographic factors in patients participating in early phase clinical trials. Methods: We conducted a study to assess baseline FT in English-speaking patients (pts) with advanced metastatic solid tumors who were participating in EPTs at the Yale Cancer Center (Yale) and the Tisch Cancer Institute at Mount Sinai (Sinai). Pts were consented after EPT consent and prior to day 1 of study treatment. Pts completed a clinical and demographic questionnaire as well as the 11-item validated Comprehensive Score for Financial Toxicity (COST) FT instrument. Primary endpoints included baseline FT and association with clinicodemographic variables. Statistical analysis was performed using two-sided T-tests and Pearson correlations for numeric data and Fisher's Exact Test for categorical data. Multivariate analysis was performed using a linear regression model. Results: 138 pts enrolled in this study, of whom 132 completed the COST instrument (Yale, N = 84; Sinai, N = 48). Median age was 62 and 49.2% were male. 71.2% patients self-identified as White and 15.2% as Black; 7.2% identified as Hispanic. 32.6% reported an annual income of < 50, 000. Insurance providers included private insurers (50%), Medicare (31.8%), Medicaid (10.6%), and Medicaid with Medicare supplemental (3.8%). 56.8% reported monthly out of pocket medical expenses of 100 or more. Median FT score was 22.5 out of a maximum score of 44 (mean 21.5). FT scores ≥ 22.5 in pts were associated with age < 65 (OR = 2.229, P = 0.04), being the household money manager (OR = 2.98, P = 0.02), and being the primary wage earner (OR = 3.12, P = 0.004). FT scores < 22.5 in pts was associated with retirement (OR = 0.15, P = 3.67e-05). In multivariate analysis, retirement was associated with FT score < 22.5 (OR = 0.18, P = 0.02). There was no statistically significant difference in FT scores between Yale and Sinai pts. However, Sinai pts were more racially diverse (p = 3.05e-05), had lower household income (P = 0.01), out of pocket expenses (P = 0.01), ED visits (P = 0.0075), and dependents (P = 0.004) and were less likely to have private insurance (P = 0.004). Conclusions: Pts with advanced cancers consenting to EPTs report significant baseline FT. Our study encompasses a diverse population from two large urban academic centers. Baseline FT was higher among pts < 65 years of age, primary wage earners, and those who managed household finances independently. Retirement was a protective factor, which may be explained by the life savings often required to retire. Ongoing work will compare baseline and 2 month FT in this patient population.